Working from home (WFH): a new way of working in post COVID-19 era / Norhazlan Haron ... [et al.] - Haron, Norhazlan; Zainol, Halmi; Wan Omar, Wan Rabiah; Sallehudin, Noor Syarafina (2021)
Working from Home (WFH) is a new way of working. It is based on information and communication technologies which are rapidly replacing the old method of working. It was started at the beginning of 2020, because of the World Pandemic Issue, Covid-19. Since the 1st case of Coronavirus on 25 January 2020, until today, the pandemic transforms and acts as a catalyst for change in urban development and lifestyle. Thus, Covid-19 has changed the landscape of development in Malaysia and globally by disrupting the economic ecosystem. WFH provides an opportunity and steps to implement physical distancing within achieving sustainable and resilient growth within pandemic Covid-19. This new way of working has managed to reduce the problem of vehicles, the rapid growth of the commercial area in cities. The rapid growth of residential development in the urban fringe has caused the CBD to function as the employment centre. It is forcing the workers to generate trips to their office. The purpose of this study is to determine the overall WFH concept as a new way of working. Content analysis was used to identify the contributing factors that influence WFH. One of the main factors is efficiency in working which has been identified as significant in contributing to WFH behaviour. Traffic congestion, travel expenses and related costs such as car park, fuel and maintenance costs had been reduced. From the analysis, all the factors have been listed to contribute a new conceptual framework of Working from Home. The study has found that the acceptance of WFH will become a new way of working in this pandemic and improve sustainable development and resilience.